Methane emission and nutritive evaluation of green, black, oolong, and white tea leaves - SRI WAHYUNI; ASEP SUDARMAN; AHMAD SOFYAN; DESSY PERMATA; I NYOMAN GUNA DARMA; DIKY RAMDANI; NANIK HIDAYATIK; ANURAGA JAYANEGARA (Society for Indonesian Biodiversity, 2025)
Abstract. Wahyuni S, Sudarman A, Sofyan A, Permata D, Darma ING, Ramdani D, Hidayatik N, Jayanegara A. 2025. Methane emission and nutritive evaluation of green, black, oolong, and white tea leaves. Biodiversitas 26: 3423-3433. This study aimed to evaluate the impact of non-fermented and fermented leaves of green tea, black tea, oolong tea, and white tea on nutritive value, methane emission, and in vitro ruminal fermentation characteristics. Each type of tea leaves was prepared in both fresh (non-fermented) and fermented forms. Fermented tea leaves were treated with water in a 1:2 ratio. Each treatment was prepared in five replicates and incubated for 30 days. A completely randomized factorial design was applied, with tea type as the primary factor and fermentation status (non-fermented and fermented) as the secondary factor. Results revealed that the highest crude protein content was found in white tea (29.41%), followed by green tea (17.87%). There was a significant effect (p<0.05) of tea types on IVDMD and IVOMD, with fresh oolong tea exhibiting the highest value and white tea the lowest. Excellent fermentation profiles were observed among different tea types (p<0.001) regarding gas production after 48 hours, with fresh green tea producing the highest amount. The highest methane production was observed in fermented green tea (2.35%), while the lowest was in fermented oolong tea (0.89%). Fermented oolong tea as a feed additive in ruminant diets may reduce enteric methane production, potentially improving feed efficiency. In conclusion, fermentation is able to maintain the nutritional quality of tea leaves but the effect on methane emission is varied.